'So how was it for you? Students with disabilities transitioning to higher education: a mixed methods study. - SHEVLIN, MICHAEL; MCGUCKIN, CONOR; DOYLE, ALISON (My University, 2013)
This paper describes the methodological framework for a large scale longitudinal study examining the experiences of students with disabilities transitioning from 6th year of secondary school to higher education. The study combines inductive and deductive logics of enquiry using 1) college application and admissions data collated from one HEI, and 2) personal viewpoints collated via an online survey and discussion forum. This study was designed as a concurrent-transformative-triangulation-convergent Mixed Methodology with equal weighting and merged results delivered in two sequential phases. Research questions examine access to opportunities, and support and guidance through the transition process from the perspective of students, parents and practitioners within the education system, as stakeholders in the process. The strategic and structural elements of the research process are discussed with reference to the appropriateness of the epistemology, theoretical perspective, methodology and methods of data collection.
PUBLISHED
Keywords: Disability Students